Food Security and Dietary Diversity: A Phenomenological Study of Smallholder Farmers in Rural Communities, Central Region - Vandyck, N.A.A. (University of Ghana, 2022)
Food insecurity, poverty, limited diet quality and diversity are significant global problems. Several households rely on crops and livestock to meet their dietary needs. Smallholder farmers are primary producers of food consumed in rural areas. However, when it comes to food insecurity, they are the most vulnerable group. This study was conducted to investigate the perspectives of smallholder farmers on food security and dietary diversity in rural areas in the Central Region of Ghana. The study employed a qualitative approach using a phenomenological study design. The study location was three (3) rural communities; Atonkwa, Abbina and Kuful, all located within the Elmina township. A total of thirty (30) smallholder household heads were selected through a multi-stage sampling method. Thematic content analysis was used to analyse the data collected. The predetermined themes were organised food availability and access, causes of food insecurity, determinants of dietary diversity and coping strategies. Twelve (12) sub-themes emerged from the interviews conducted. The findings indicated that the perceived causes of food insecurity were based on socioeconomic factors and climate variability, affecting the availability and access to food. The diversity of food consumed within the household was determined by household food production, socio economic factors, and information access and use. The study concluded that challenges with food availability and accessibility among smallholder farmers affect the food security status and the dietary diversity of the household. Based on the results, it was suggested that to help fix the social and economic problems that lead to food insecurity, the government should implement a comprehensive and multi-faceted approach. This approach should include; strengthening social safety nets, investing in agricultural development and improving rural infrastructure.
MPhil. Home Science
Keywords: food security; dietary diversity; Central Region; experiences; coping strategies